Cheese Fortification: Review and Possible Improvements. (1st November 2022) - Picciotti, Ugo; Massaro, Alessandro; Galiano, Angelo; Garganese, Francesca
ABSTRACT: Food fortification includes micronutrient directly added or by probiotics in food matter, making the final product more enticing to the consumers. Dairy products well represent a category of foods to fortify successfully. Fortification properly enhances cheeses, including micronutrients into the casein matrix. The process exalts either nutritional or technological product features. Food fortification occurs with the adding of primary or secondary compounds from the agrifood production chain. Using vegetable by-products encourages circular economy, generating an eco-sustainable and consumer health-promoting compounds class. Organic compounds of interest result from probiotic microorganism's activity, offering micronutrients to "enrich" the profile of the exalted cheese. Allogeneic probiotics may originate from specialised insects-borne microbiota. The latter class offers new challenges to improve the nutritional and sensorial profiles of cheeses. The review focuses on food fortification frameworks; cheese fortification approaches; microencapsulation and stabilisation; cheese fortification with mineral elements; cheese fortification with essential micronutrients; fortification with by-products of the agrifood industry; fortification with microorganisms. The review considers the cheese matter a driver and an operating carrier for elements and organic compound as vitamins, carotenoids, polyphenols and essential fatty acids. Organic compounds of interest result from probiotic microorganisms' activity are enzymes, antimicrobial compounds, short-chain fatty acids and some vitamins (A and D). Specialised insects-borne microbiota confers typical smells, flavours, consistency and nutritional attributes, respecting high hygienic-sanitary standards. The review aims to summarise in a single text the techniques, micronutrients and microorganisms most used for Market-Driven Cheese Fortification. Also, there is no review in the literature that includes all these aspects together. The paragraphs are concise dissertations on the nutraceutical, technological and sensory properties of the most widely used fortifiers in cheese. The information reported derived from an in-depth analysis of the literature from 1977 to 2020.